Optimalisasi Mapping Research: Pelatihan Aplikasi VOSviewer dalam Meningkatkan Kualitas Penelitian Mahasiswa - Bato, Bulan Erika; Bambang Irawan; Yulia Prihartini; Gusti Naufal Rizky Perdana (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2025)
This training activity aims to enhance students’ abilities to utilize software for bibliometric mapping and research visualization as part of supporting data-driven academic writing. The implementation methods include a pre-test to measure students’ knowledge, user book guide preparation, and workshops followed by evaluations of students’ understanding before and after the training. The results show a significant improvement in students’ ability to identify, analyze, and visualize research data using the taught software. The conclusion of this activity is that the training positively impacts students’ ability to use technology to support academic research and increases their understanding of the importance of data visualization in scientific publications.